Synthesis, reactivity and modification of novel meso-substituted porphyrins - Dahms, Katja (Trinity College (Dublin, Ireland). School of Chemistry, 2008)
The aim of this work was the synthesis, modification and characterisation of novel meso- substituted porphyrins. In particular, focus was directed towards the development of new synthetic pathways and the improvement of existing preparative methods. Two different synthetic methods for the introduction of the formyl residue into the meso- position of the porphyrin macrocycle were investigated, together with studies of its transformation into a variety of functional groups. 1,3-Dithianylsubstituted porphyrins were used as synthons. Dithianylporphyrins can be synthesised by condensation reactions, with the mixed condensation versions giving rise to more stable derivatives. Alternatively, new C-C bonds were formed via organolithium compounds. Free base and the nickel(ll) porphyrins were synthesised using 2-lithio-1,3-dithiane as the organolithium reagent. The products were stable but butylation occurred as a competitive reaction. Formylporphyrins were received from the dithianylporphyrins via acid-catalysed deprotection. A variety of copper(ll) and nickel(ll) formylporphyrins were also synthesised in moderate to high yields by the Vilsmeier reaction. Grignard and Wittig reactions on a series of formylporphyrins were performed to demonstrate the wide application range of the formyl group as a precursor for obtaining more elaborately functionalised porphyrin molecules.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin